Research and Improvement of Employee Motivation in Mining Companies: A Case Study of “Ibarski Rudnici”, Serbia - Bozovic, Jelena; Bozovic, Ivan (International Review of Management and Marketing, 2019)
Research has been conducted to examine the effect of work motivation, work environment and incentives on the employee satisfaction in one of the most important mines in Serbia called "IBARSKI RUDNICI". The empirical research was conducted in the period from September to November 2018, and 49 employees were examined. The questionnaire is compounded by the Likert’s five-stage scale. In this study, the T-test is useful as part of the analysis used to test the satisfaction of the various aspects of the work. One-factor analysis (ANOVA) was applied for the research of the desirable characteristics of the manager in the work. Such a sample may not be fully representative, but is sufficiently informative in any case, since it can be concluded that some factors influence the work motivation in the analyzed company. The data was processed with the statistical package IBM SPSS Statistic 20. for Windows shows that: There is a positive and significant influence on the working motivation of employee satisfaction in the mining company. The analyzed models for investigating the motivation of employees indicate that a real managerial approach implies real knowledge and monitoring of employee preferences and preferences, as well as adequate material and non-material incentives, but also desirable qualities that each manager should possess. Keywords: Work Motivation, Mining Company, Employee Job Satisfaction. JEL Classifications: M12, M54, L0, Q3 DOI: https://doi.org/10.32479/irmm.7464